Comments on supergravity description of S-branes - Buchel, Alex; Walcher, Johannes (Journal of high energy physics, 2003)
This is a note on the coupled supergravity-tachyon matter system, which has been earlier proposed as a candidate for the effective space-time description of S-branes. In particular, we study an ansatz with the maximal ISO( p +1) × SO(8− p ,1) symmetry, for general brane dimensionality p and homogeneous brane distribution in transverse space ρ ⊥ . A simple application of singularity theorems shows that (for p ≤ 7) the most general solution with these symmetries is always singular. (This invalidates a recent claim in the literature.) We include a few general comments about the possibility of describing the decay of unstable D-branes in purely gravitational terms.